2010
DOI: 10.1016/j.otohns.2010.06.312
|View full text |Cite
|
Sign up to set email alerts
|

The Friedman Tongue Score Can Predict Sleep Apnea Severity

Abstract: (large mucous cysts, choanal polyp,). PIEC includes: severe not correctable anatomic impairment of the nasal wall or antral mucosa (post-traumatic, post-surgical, or post-radiotherapeutic scars); naso-sinusal inflammation associated with systemic conditions (cystic fibrosis, Kartagener's and Young's syndrome, congenital or acquired immunodeficiency, Wegener's granulomatosis, sarcoidosis); extensive naso-sinusal neoplasms (inverted papilloma, fibroma, lymphomas, primary and metastatic malignancies). CONCLUSION:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Barcelo et al has analysed predicators of severe forms of OSA and has found that tonsil size, BMI, neck circumference, age and gender are associated with the severity of OSA, but Mallampati class is statistically the most significant predicator [28].…”
Section: Bmi_t0 Bmi_t0mentioning
confidence: 99%
“…Barcelo et al has analysed predicators of severe forms of OSA and has found that tonsil size, BMI, neck circumference, age and gender are associated with the severity of OSA, but Mallampati class is statistically the most significant predicator [28].…”
Section: Bmi_t0 Bmi_t0mentioning
confidence: 99%